HCV reinfection incidence among individuals treated for recent infection. Issue 5 (23rd January 2017) - Martinello, M.; Grebely, J.; Petoumenos, K.; Gane, E.; Hellard, M.; Shaw, D.; Sasadeusz, J.; Applegate, T. L.; Dore, G. J.; Matthews, G. V.
Summary: One challenge to HCV elimination through therapeutic intervention is reinfection. The aim of this analysis was to calculate the incidence of HCV reinfection among both HIV‐positive and HIV‐negative individuals treated for recent HCV infection (estimated infection duration <18 months). Individuals with recent HCV infection who achieved an end‐of‐treatment response in four open‐label studies between 2004 and 2015 in Australia and New Zealand were assessed for HCV reinfection, confirmed by sequencing of the Core‐E2 and/or NS5B regions. Reinfection incidence was calculated using person‐time of observation. Exact Poisson regression analysis was used to assess factors associated with HCV reinfection. The cohort at risk for reinfection ( n =120; 83% male; median age 36 years) was composed of HIV‐positive men‐who‐have‐sex‐with‐men (53%) and people who inject drugs (current 49%, ever 69%). Total follow‐up time at risk was 135 person‐years (median 1.08 years, range 0.17, 2.53). Ten cases of HCV reinfection were identified, for an incidence of 7.4 per 100 py (95% CI 4.0, 13.8). Reinfection incidence was significantly higher among participants who reported injection drug use at end of or post‐treatment, irrespective of HIV status (15.5 per 100 py, 95% CI 7.8, 31.1). In adjusted analysis, factors associated with reinfection were older age (aIRR 5.3, 95% CI 1.15, 51.5, P =.042) and injection drug use at end of or post‐treatment (aIRR 7.9, 95% CI 1.6, 77.2, P =.008). High reinfection incidence following treatment for recent HCV infection in individuals with ongoing risk behaviour emphasizes the need for post‐treatment surveillance, harm reduction strategies and education in at‐risk populations.